Determination of the fracture energy in polymeric films by in situ photoelasticimetry on double edge notch specimen. Issue 1 (9th September 2015) - Dubelley, Florence; Planes, Emilie; Bas, Corine; Yrieix, Bernard; Flandin, Lionel
ABSTRACT The fracture toughness is key parameters to select polymeric films. The essential work of fracture (EWF) is a phenomenological but efficient way to characterize this resistance to fracture. One can gain valuable information on the resistance to perforation and propagation of flaws. A new technique was developed to better understanding the EWF experiments. A tensile test combined to photoelasticimetry allows following in situ the geometry and amount of plastic deformation on double edge notched specimen. The EWF parameters are determined when the plastic deformation appears constant, so when the fracture energy Wf only contributes to rupture filament. This new methodology requires just a single sample, whereas at least five specimens are required for general method. It will help characterize expensive polymeric films or reveal the heterogeneous behavior, for instance after polymer ageing. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2016, 132, 42854.